Manajemen Perioperatif Seksio Sesarea Pasien G2P1A0 Hamil 38 Minggu dengan Plasenta Akreta dan Plasenta Previa Totalis - Fajar A, Ratih Kumala; Jufan, Akhmad Yun; Kuncoro, Kusuma Edhi (Jurnal Komplikasi Anestesi, 2019)
Placenta accreta is becoming more common and is the most frequent indication for peripartum hysterectomy. Management of cesarean delivery in the setting of a morbidly adherent placenta has potential for massive hemorrhage, coagulopathies, and other morbidities. Anesthetic management of placenta accreta presents many challenges including optimizing surgical conditions, providing a safe maternal delivery, preparing for massive hemorrhage and transfusion, preventing coagulopathies, and optimizing postoperative pain control. Balancing these challenging goals requires meticulous preparation with a thorough preoperative evaluation of the parturient and a well-coordinated multidisciplinary approach in order to optimize outcomes for the mother and fetus.